Investigation of transverse residual stresses in a thick pultruded composite using digital image correlation with hole drilling. (1st September 2019) - Yuksel, Onur; Baran, Ismet; Ersoy, Nuri; Akkerman, Remko
Abstract: Process induced residual stresses are one of the main sources of defects such as (pre) mature matrix cracking during pultrusion of fiber reinforced polymer composite profiles. Recently, comprehensive process models have been developed to understand and describe the underlying mechanisms of the residual stresses in pultrusion processes. The predicted stresses however have not been validated with experimental measurements which are necessary to verify the implemented material models and assumptions in the process models. A hole drilling method with digital image correlation (DIC) is used in the present work to measure the transverse strain relaxation due to material removal in a pultruded thick composite profile (20  ×  20 mm) made of unidirectional glass/polyester. The corresponding residual stress state is back calculated using the measured strains in a finite element based numerical model. The estimated level of transverse residual stress in the core of the profile was found to be 6.1 MPa in tension.